"Vê se me desimbaça": do apelo à demanda de crianças e adolescentes em situação de rua - Barros, Paula Cristina Monteiro de (2009)
The street boys are related to a complex reality of social exclusion to which thousands of children and adolescents are submited. This reality, perpassed and constitued by social, economicals, politics, cultural and historical factors, has a tendency to occult what exists as singular in the history, in the suffering, in the families dynamics, in the lives of subjects that, in front of experienced conflicts and also considering the role of dejection in the social context, adopt the same exit in order to the existence be possible (CAMPOLINA, 2001): the street. Children and adolescents, thus, left in a way that reveal to them the most rude and real face of the exclusion, of the abandonment, of the poverty, of the violence which has a tendency to reproduce in the circulation among different spaces the house in the street, the institutions but also trying to find a possible way of addressing that recognize them as subjects. If this search always exists, or if they are searching. This research was developed in this way, based in an experience at one institution that takes care of children and adolescents in street s situation. Vinculated to the research project of Frej (2007), Limits, barriers and addressment among mother and child , this research had as objective understand the demand addressed by children and adolescents in street s situation to the institution. The continuous transgression, the destructiveness in the relationship with the institution, furthermore, the expressions as Make me blurred anymore , You are a search-trash , make possible suppositions about appeal, demands addressed to the institution. The psychoanalitic theory, fundamentally the formulations of Freud and Lacan, as well as Bergès e Balbo, brought important constributions to understand the demand, the appeal, the addressment, the play of positions between the subject and the Other. The research analysed data from the registers of the institution with the major purpose to contextualize the public and consider especificities in the attendance. Moreover, discussed three clinical cases, with the objective to, in the passage of the adolescents in the institution, articulate questions concernents to the demand that they have addressed. From the discussions made, we suggested that the institution as a space of addressment ( treasure of significants ) which, making a hypotheses of an appeal to the shouts of help of children and adolescents in street s situation, constitue itself as a place that receive, interdict, nominate, delimitate, and symbolize beyond of the real of the street. A place that when register the subject in the language domain thus, in another position -, institute the bet and the possibility that, in the appeal Make me blurred anymore see indistinctly the building and the addressment of demands to the institution. Key-words: Children and adolescents in street s situation, appeal, demand, institution, addressment